MPACT OF ADULTHOOD LIFESTYLE ON MALE INFERTILITY: A CRITICAL REVIEW OF THE CURRENT LITERATURE : Life Science-Physiology - PRAMANIK, PURUSHOTTAM (International Journal of Life Science and Pharma Research, 2012)
Human infertility has been increasing worldwide but the exact causes are not yet known. Male infertility, which currently accounts for approximately half of all cases, has been increasing faster than female. While certain cases of male infertility are due to anatomical abnormalities, an estimated 40-49% of cases are due to deficient sperm production of unidentifiable origin. There is growing body of scientific evidence supporting the idea that sperm counts have declined considerably over the last 50 years. Over the last few decades, there have been progressive changes in aspects of our diet, lifestyle as well as environment. Report in recent years has shown that the incident of male infertility has increased as a result of various factors such as environmental pollution, stress and lifestyle. Among lifestyle, factors such as tobacco smoking, smokeless tobacco chewing, alcohol intake, high temperature, some modern electronic gadget and obesity have shown to adversely affect reproduction. These factors may impair male fertility by interfering with spermatogenesis, spermiogenesis, motility, sperm DNA and chromatin integrity, hormonal regulation or by reducing the fertilizing capacity of spermatozoa. Most of the lifestyle factors decrease semen quality by inducing oxidative stress from imbalance between rate of formation of reactive oxygen species and their scavenging capacity by antioxidant system. In conclusion it is strongly encouraged to research into antioxidants for greater understanding of the effects of ROS on sperm parameters and it will be beneficial way of finding solutions to human male infertility.